Spectral differentiation of oak wilt from foliar fungal disease and drought is correlated with physiological changes. (6th February 2020) - Fallon, Beth; Yang, Anna; Lapadat, Cathleen; Armour, Isabella; Juzwik, Jennifer; Montgomery, Rebecca A; Cavender-Bares, Jeannine
Abstract: Hyperspectral reflectance tools have been used to detect multiple pathogens in agricultural settings and single sources of infection or broad declines in forest stands. However, differentiation of any one disease from other sources of tree stress is integral for stand and landscape-level applications in mixed species systems. We tested the ability of spectral models to differentiate oak wilt, a fatal disease in oaks caused by Bretziella fagacearum ``Bretz'', from among other mechanisms of decline. We subjected greenhouse-grown oak seedlings ( Quercus ellipsoidalis ``E.J. Hill'' and Quercus macrocarpa ``Michx.'' ) to chronic drought or inoculation with the oak wilt fungus or bur oak blight fungus ( Tubakia iowensis ``T.C. Harr. & D. McNew'' ). We measured leaf and canopy spectroscopic reflectance (400–2400 nm) and instantaneous photosynthetic and stomatal conductance rates, then used partial least-squares discriminant analysis to predict treatment from hyperspectral data. We detected oak wilt before symptom appearance, and classified the disease with high accuracy in symptomatic leaves. Classification accuracy from spectra increased with declines in photosynthetic function in oak wilt-inoculated plants. Wavelengths diagnostic of oak wilt were only found in non-visible spectral regions and are associated with water status, non-structural carbohydrates and photosynthetic mechanisms. We show that hyperspectral models can differentiate oak wilt from other causes of tree decline and that detection is correlated with biological mechanisms of oak wilt infection and disease progression. We also show that within the canopy, symptom heterogeneity can reduce detection, but that symptomatic leaves and tree canopies are suitable for highly accurate diagnosis. Remote application of hyperspectral tools can be used for specific detection of disease across a multi-species forest stand exhibiting multiple stress symptoms.